Seasonality and paving affect roadkill rates on a highway in Cerrado biome, Brazil - Pereira, Wanessa Gomes; Assis, Jasmine de Resende; Basile, Isabela Solha; Iannini-Custódio, Ana Elizabeth; Carvalho-Roel, Carine Firmino (Ethnobiology and Conservation, 2025)
Wildlife roadkill poses a significant global threat to biodiversity, with heightened concerns in Protected Areas, such as the Panga Ecological Station (PES) located in the Cerrado biome, Minas Gerais state, Brazil. Throughout this research, the adjacent highway to the PES, MGC-455 highway, underwent paving. To assess roadkill rates and explore the potential impact of seasonality and road pavement type, bimonthly monitoring was conducted along the highway. The survey spanned 35 km of paved and 10 km of unpaved road from April 2012 to April 2013, and 50 km of paved and 30 km of unpaved road from May 2013 to April 2015, covering a total distance of 4,820 km. Despite the extended survey period, progress in the highway’s paving remained minimal. A total of 87 individuals were identified, comprising 38 birds, 24 reptiles, 17 mammals, and eight amphibians. Across the documented species (37 in total), there were 15 bird species, 12 reptile species, eight mammal species, and two amphibian species. The roadkill rate for wild vertebrates was 0.008 individuals/km/day, likely underestimated. Reptile roadkill was notably prevalent during the rainy season. Roadkill rates were approximately six times higher on paved stretches (0.006 individuals/km/day) compared to unpaved sections (0.001). The presence of endangered species in the area emphasizes the ongoing need for monitoring roadkill, particularly with the anticipated rise in roadkill rates due to the continued highway paving. Future comparisons can be drawn between our data and post-paving roadkill rates to assess potential increases.